FOOD INSECURITY AND CHILDHOOD OBESITY: A SYSTEMATIC REVIEW - Setiawati, Ferianis; Prima Dewi, Anis (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Food security for children is a public health issue. Childhood food insecurity is a major public health issue in low-income and developing nations. The 2011–2012 prevalence of childhood obesity was 16.9%, despite a plateau. The link between the two is crucial for proper management.Objective: this systematic review will further discuss the relationship between food insecurity and the occurrence of obesity in childhood.Methods: This systematic review used PRISMA guideline, the database used is PubMed, Web of Science, dan Science Direct. ((Food) AND (Insecurity) AND (Relation) OR (influence) AND (Pediatric) OR (Children) AND (Obesity) OR (Fat) OR (Nutritional status)) are used as keywords. Additionally, manual searches are conducted to obtain articles that satisfy the specified criteria. Discrepancies are resolved through consensus with the third author.Results: There were a total of 12,574 cases included in the study. With ages ranging from five to eighteen. Ethiopia, Canada, the U.S., and Atlanta are among the origins of the research. With investigation years spanning from 2014 to 2022. Children's lack of physical exercise, irregular intake patterns, excessive consumption out of fear of food deterioration, and occasional fruit and vegetable consumption contribute to obesity in food-insecure groups. Majority of population has poor socioeconomic conditions. Conclusion: Food insecurity is linked to obesity in families. This depends on several things. Childhood obesity management emphasises education and self-efficacy to eat well.